2013
DOI: 10.3390/cancers5010149
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma-Associated Fibroblasts Are a Promising Therapeutic Target

Abstract: Human carcinomas frequently exhibit significant stromal reactions such as the so-called “desmoplastic stroma” or “reactive stroma”, which is characterised by the existence of large numbers of stromal cells and extracellular matrix proteins. Carcinoma-associated fibroblasts (CAFs), which are rich in activated fibroblast populations exemplified by myofibroblasts, are among the predominant cell types present within the tumour-associated stroma. Increased numbers of stromal myofibroblasts are often associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
115
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(115 citation statements)
references
References 112 publications
(212 reference statements)
0
115
0
Order By: Relevance
“…These data are consistent with the ability of ErbB3-targeting agents to increase the efficacy and duration of response of RAF inhibitors in vivo (15) and underscore the use of ErbB3-targeting agents to reduce the protective effects of fibroblast-derived NRG1 on RAF-inhibited melanoma cells. Although pertuzumab and seribantumab target ErbB3/ErbB2 signaling by preventing ErbB3/ErbB2 dimerization or the binding of NRG1 to ErbB3, respectively, other agents may be developed to directly sequester NRG1 (45) or to directly target CAFs (46). Our findings also have relevance to other tumor types in which ErbB3 has been implicated in driving resistance to targeted inhibitors (19,20).…”
Section: Discussionmentioning
confidence: 52%
“…These data are consistent with the ability of ErbB3-targeting agents to increase the efficacy and duration of response of RAF inhibitors in vivo (15) and underscore the use of ErbB3-targeting agents to reduce the protective effects of fibroblast-derived NRG1 on RAF-inhibited melanoma cells. Although pertuzumab and seribantumab target ErbB3/ErbB2 signaling by preventing ErbB3/ErbB2 dimerization or the binding of NRG1 to ErbB3, respectively, other agents may be developed to directly sequester NRG1 (45) or to directly target CAFs (46). Our findings also have relevance to other tumor types in which ErbB3 has been implicated in driving resistance to targeted inhibitors (19,20).…”
Section: Discussionmentioning
confidence: 52%
“…The realization of these biological links justifies the design of clinical studies based on the targeting of CAF (and, more generally, reversal of the attributes of a protumorigenic microenvironment) in addition to targeting cancer cells in order to create a tumor-resistant environment that inhibits malignant phenotypes in diseased epithelial cells (Takebe et al 2013;Togo et al 2013;Zhou et al 2015). Such clinical studies can now be envisioned based on the findings from experimental studies with agents directed against fibroblast-specific proteins (FAP, COL11A1, and MFAP5) or signaling pathways exemplified in CAFs (TGF-β, hedgehog, Notch, FGF, PDGF, or C-X-C motif ligand 2 [CXCL2]/CXCR4 signaling).…”
Section: Acquisition Of a Caf State: Therapeutic Opportunitiesmentioning
confidence: 99%
“…***p < 0.001 compared with all other groups. therapeutic target [28,29]. However, it has also been recently suggested that not all of the fibroblasts within a tumor are harmful to the patient; carcinoma associated fibroblasts are able to express both tumor promoting and tumor suppressing molecules simultaneously [4,5].…”
Section: Fig 4 Induction Of Luciferase In Spheroids (A)mentioning
confidence: 99%